Thermal Assessment of Buildings Based on Occupants Behavior and the Adaptive Thermal Comfort Approach. (June 2017) - Albatayneh, Aiman; Alterman, Dariusz; Page, Adrian; Moghtaderi, Behdad
Abstract: The adaptive approach promotes sustainable ways for the occupants to obtain thermal comfort using strategies such as natural ventilation (opening and closing windows), suitable clothes and shading. When applied to typical housing modules, the adaptive approach reduced the time required for mechanical heating or cooling by more than half compared with a typical energy based approached (AccuRate). The study was performed for four test modules located in Newcastle, Australia incorporating four different walling types (Cavity Brick, Insulated Cavity Brick, Insulated Brick Veneer and Insulated Reverse Brick Veneer) subjected to a range of seasonal conditions in a moderate climate.